Study on Science and Biology Practicum in Middle Schools during the COVID-19 Pandemic - Putri Agustina; Alanindra Saputra; Irfan Akbar; Sania Rahayu (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
Biology learning in accordance with its essence should emphasize direct experience so that students are able to explore the natural surroundings scientifically. Practicum is a vehicle to provide direct experience to students. However, due to the COVID-19 pandemic and the implementation of distance learning, the implementation of the practicum cannot run as it should. The purpose of this study was to describe the implementation of Biology/Science practicum in secondary schools during the COVID-19 pandemic T.A 2020/2021. This research is a descriptive study that was conducted from February to July 2021. The subjects of this research were Biology and Science teachers in high schools throughout Solo Raya. The data was taken by using a questionnaire technique which was distributed through google form. The number of respondents in this study were 41 people. The results of the questionnaire analysis on the implementation of Biology and Science practicums in high schools throughout Solo during the COVID-19 pandemic, it was found that 65.9% carried out practicums during the COVID-19 pandemic while 34.1% did not carry out practicums. The implementation of the practicum uses various platforms such as google meet and moodle app, zoom meeting and youtube, google classroom, and so on. Regarding the effectiveness of online practicum implementation, 92.7% said it was not effective while 7.3% said it was effective.